LOCAL ELECTIONS IN ZAJEČAR AND KOSJERIĆ, 2025 - Mijatović, Marko (Political Review, 2025)
The regular local elections in the city of Zaječar and the municipality of Kosjerić, held on June 8, 2025, represented the first vote of Serbian citizens in the two local governments mentioned above, in the changed socio-political circumstances caused by the Novi Sad tragedy on November 1, 2024, in which sixteen people died after the collapse of a canopy at the Railway Station, and which culminated in student demonstrations that began at the end of the same month, first by students and professors of the Faculty of Dramatic Arts, and then by other faculties and universities in Serbia, which gained momentum in early 2025 and culminated with a protest in Belgrade in mid-March that gathered several hundred thousand people.The involvement of students (or as we will call the student movement in the text) significantly changed the political landscape of Serbia – through, as public opinion polls have shown – a decline or even stagnation in the popularity of the ruling party, but also of opposition parties, with a sharp increase in the popularity of the student movement as a potential future political force. The first opportunity to demonstrate the new balance of political forces was the regular local elections in Zaječar and Kosjerić, scheduled for June 8, 2025. Although the opposition lists, with the support of the student movement, failed to win, their success turned out to be far more significant than in previous elections in these local governments.
Keywords: Local elections; Republic of Serbia; Political parties; City of Zaječar; Municipality of Kosjerić